(untitled) (Amsterdam, 2005)
The book begins with the Overview modude and you should complete it before any other modules. It contains a functional overview of the essential tools and principles of 3ds max. The modude starts with an introduction to 3D animation and how to use 3ds max.
Keywords: 3ds max ( Computer programs )